A novel human stem cell platform for probing adrenoceptor signaling in iPSC derived cardiomyocytes including those with an adult atrial phenotype - Ahmad, F (2017)
Scientific research is propelled by two objectives: Understanding and recognizing the essential biology of life, and deciphering this to uncover possible therapeutics in order to improve quality of life as well as relieve pain from disease. The aim of the work described in this thesis was to dissect the fundamental requirements of induced pluripotent stem cells both in pluripotency and differentiation with a particular focus on atrial specificity. Drug targeting of atrial-specific ion channels has been difficult because of lack of availability of appropriate cardiac cells, and preclinical testing studies have been carried out in non-cardiac cell lines, heterogeneous cardiac populations or animal models that have been unable to accurately represent human cardiomyocyte physiology. Therefore, we sought out to develop a preparation of cardiomyocytes showing an atrial phenotype with adult characteristics from human induced-pluripotent stem cells. A culture programme involving the use of Gremlin 2 allowed differentiation of cardiomyocytes with an atrial phenotype from human induced-pluripotent stem cells. When these differentiated cultures were dissociated into single myocytes a substantial fraction of cells showed a rod-shaped morphology with a single central nucleus that was broadly similar to that observed in cells isolated from atrial chambers of the heart. Immunolabelling of these myocytes for cardiac proteins (including RyR2 receptors, actinin-2, F-actin) showed striations with a sarcomere spacing of slightly less than 2um. The isolated rod-shaped cells were electrically quiescent unless stimulated to fire action potentials with an amplitude of 100 mV from a resting potential of approximately -70 mV. Proteins expressed included those for IK1, IKur channels. Ca2+ Transients recorded from spontaneously beating cultures showed increases in amplitude in response to stimulation of adrenoceptors (both alpha and beta). With the aim of identifying key signaling mechanisms in directing cell fate, our new protocol allowed differentiation of human myocytes with an atrial phenotype and adult characteristics that show functional adrenoceptor signaling pathways and are suitable for investigation of drug effects.